Pembaruan sistem pendidikan Islam: Sekolah Islam Terpadu - Frandani, Muhammad (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2023)
If compared, Islamic education in Indonesia is like a train that has been running on a track for a very long time, passing through cool and hot nature. traversing steep valleys, pitch-dark jungles, and various obstacles, as forges for the path of Islamic education in the archipelago. When talking about the modernization of Islamic education, experts focus more on three objects of study, namely Islamic boarding schools, madrasas, and tertiary institutions. Meanwhile, school brands do not get a major place among Islamic education researchers. Only a few researchers or educational thinkers have a focus on Islamic educational institutions called schools. So it becomes interesting when there is a study related to the Integrated Islamic School (SIT), so that various efforts of "Muslim elites" can be identified in the development of the Islamic education system. This research is a historical study of Islamic education that uses two approaches, namely the historical approach and the descriptive approach. The research results show that although the emergence of integrated Islamic schools is a response to dissatisfaction with educational practices in Indonesia, until now, integrated Islamic schools remain an integral part of the national education system. Abstrak         Jika diibaratkan, pendidikan Islam di Indonesia laksana kereta yang sudah berjalan di lintasan waktu yang sangat panjang, melewati alam yang sejuk dan terik. melintasi lembah yang terjal, hutan rimba yang gelap gulita, serta berbagai aral melintang, sebagai tempaan jejak jalan pendidikan Islam di Nusantara. Ketika berbicara tentang modernisasi pendidikan Islam, para pakar lebih fokus kepada tiga objek studi, yaitu pesantren, madrasah, dan perguruan tinggi Islam. Sementara brand sekolah tidak mendapatkan tempat yang utama di kalangan peneliti pendidikan Islam. Hanya sedikit peneliti ataupun pemikir pendidikan yang mempunyai fokus terhadap institusi pendidikan Islam yang disebut sekolah. Maka menjadi menarik tatkala terdapat kajian yang berkenaan dengan Sekolah Islam Terpadu (SIT), sehingga dapat diketahui berbagai upaya “kalangan elite muslim” dalam perkembangan sistem pendidikan Islam. Penelitian ini merupakan penelitian sejarah pendidikan Islam yang menggunakan dua pendekatan, yaitu pendekatan historis dan pendekatan deskriptif. Hasil penelitian menunjukkan bahwa meskipun munculnya sekolah Islam terpadu merupakan respons atas ketidakpuasan terhadap praktik pendidikan di Indonesia, hingga saat ini, Sekolah Islam Terpadu tetap menjadi bagian integral dari sistem pendidikan nasional